(untitled) (Journal of Technology Research, 2025)
This study aims to analyze the forces influencing the performance of industrial institutions in the city of Misurata by applying the Force Field Analysis model, in light of the challenges these institutions face in achieving organizational and production efficiency. The research adopted a quantitative methodology through a structured questionnaire distributed to a sample of employees across nine factories. Data were analyzed using the SPSS software, employing descriptive statistics such as means and standard deviations, along with the Wilcoxon Signed-Rank Test to assess the significance of hypotheses . The results revealed that dimensions such as management, quality, and institutional constraints had a statistically significant impact on performance. In contrast, dimensions like objectives and planning did not show statistical significance, indicating a lack of strategic clarity. The study concluded that enhancing internal driving forces, minimizing institutional barriers, and adopting modern planning approaches aligned with the dynamic industrial environment are critical to improving performance.